EFEKTIVITAS PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL TENTANG MENARCHE PADA SISWI KELAS IV, V DAN VI DI SDN 03 JATEN KARANGANYAR - Suwarnisih -; Reni Puspita Sari (Jurnal Ilmiah Maternal, 2019)
ABSTRACTAdolescence is a transition period of development from childhood to adulthood, aged between 10-24 years. The changes that occur in adolescence, especially young women, one of which is the presence of menarche. Young women need to know about menarche to be better prepared for the first menstrual period. Adolescent Reproductive Health Education is very important to provide knowledge adolescents, it can be counseling, guidance, prevention, handling problems related to adolescent reproductive health education. Audiovisual media contribute greatly to changes people's behavior, especially in the aspects of information and persuasion. The purpose of this study was to determine the effectiveness of health education with audiovisual media about menarche in female students class IV, V, and VI in SDN 03 JatenKaranganyarThis study used cross sectional approach and quasy experiment design with the design of one group pre-test post-test. This design has no comparison group. The measurement process was carried out twice, namely pre-test measurement, and followed by intervention, then post-test was performed. Population in this study were all female students of grades IV, V, and VI SD N 03 JatenKaranganyar, the sampling technique used was accidental sampling with as many as 100 female students. Data analysis using t-dependent test.The results showed that the p-value was 0,000 α (0,005), meaning that there was a significant difference in mean knowledge about menarche before and after intervention. Keywords: HealthEducation, Audiovisual Media, Menarche ABSTRAKUsiaremajamerupakanperiodetransisiperkembangandari masa anakke masa dewasa, usiaantara 10 – 24 tahun. Perubahan yang terjadi pada masa remajakhususnyaremajaputri salah satunyaadalahadanya menarche. Remajaputriperluuntukmengetahuitentang menarche agar lebihsiap pada saatmengalamimenstruasi yang pertama kali tersebut. Pendidikan kesehatanReproduksiRemaja (KRR) sangatpentinguntukmemberikanbekalpengetahuankepadaremaja, dapatdiwujudkandalampenyuluhan, bimbingan dan konseling, pencegahan, penangananmasalah yang berkaitandengan KRR. Media audiovisual memberikankontribusi yang sangatbesardalamperubahanperilakumasyarakat, terutamadalamaspekinformasi dan persuasi. Tujuanpenelitianiniadalahuntukmengetahuiefektivitaspendidikankesehatandengan media audiovisual tentang menarche pada siswikelas IV, V, dan VI di SDN 03 JatenKaranganyarPenelitian ini menggunakan pendekatan cross sectional dandesainquasyeksperimentdenganrancangan one group pre-test post-test. Rancanganinitidakadakelompokpembanding. Proses pengukurandilakukandua kali yaitupengukuran pre-test, dan diikutiintervensi, kemudiandilakukan post-test.Populasidalampenelitianiniadalah seluruh siswikelas IV, V, dan VI SD N 03 JatenKaranganyar, teknikpengambilansampel yang digunakanadalahAccidental samplingdenganrespondensebanyak 100 siswi. Analisis data menggunakan t-dependent Test. Hasil penelitianmenunjukanmenunjukkannilaip-value sebesar 0,000 α (0,005), artinyaadaperbedaan yang signifikanmean pengetahuantentang menarche sebelum dan sesudahdiberikanintervensi. Kata Kunci :Pendidikan Kesehatan,Media Audiovisual,Menarche